A Model of the Effects of Gender Neutral Tenure Clock Stopping Policies on the Publication Strategies of Junior Faculty - Elisabeth Gugl; Moein Amini; Martin Farnham (Center for Economic Studies and ifo Institute (CESifo), 2022)
We model the decision of a junior faculty member where to send publications at various points along the tenure track. A single paper arrives exogenously at the start of each of three periods before the tenure decision is made. The researcher has the choice of submitting each paper to either a "Top" journal or a "Regular" journal. The probability of acceptance at a top journal is lower than at a regular journal, but the reward is greater. Researchers need a minimum of 1 top publication or 2 regular publications by the end of the three periods to get tenure. We show that, under reasonable assumptions about gendered childbearing and childrearing responsibilities, introduction of a gender neutral clock stopping (GNCS) policy induces men to submit more papers to top journals, while leaving women's submission strategies unchanged. This results in more top publications for men under a GNCS policy, while leaving women's publication records unchanged. Our model predictions are largely consistent with the empirical findings of Antecol et al. (2018). Our findings give insights into design of an important “family-friendly” university workplace policy with implications for the “leaky pipeline” in economics, whereby women are especially underrepresented at higher ranks in the discipline.
Keywords: J08; J16; M51; 330; gender neutral employment policies; tenure standards; gender roles; gender specific costs of child rearing; leaky pipeline